Condicionamento de um subsolo exposto no cerrado por meio de resíduos e da revegetação - Santos, Anderson Secco dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
To restore in an exposed subsoil, even partially, the dynamics of their attributes in the surface layer and, thus, presents conditions to receive and support the Cerrado vegetation, the use of specific techniques is required. To accelerate this step, an alternative could be the introduction of waste, such as aquatic weeds removed from water reservoirs of hydro power plants, as an organic waste, and ash sugarcane bagasse produced in sugarcane mills, as an agroindustrial waste. Thus, the objective was the conditioning of exposed subsoil in the Cerrado, through organic and inorganic waste addition and revegetation. The focus area has an extension of 10.66 km 2, in continuous area, located on the right bank of the Paraná River and degraded in the 60s during construction of the Ilha Solteira hydroelectric power. It conducted the initial characterization of the area and other evaluations were done after 12 and 24 months of implementation of the experiment. The area was fenced (heavy grade), to break the surface crusting, and scarified, at the average depth of 0.37 m. The area was again barred to break up the clods produced during the subsoil and the incorporation of waste (aquatic weeds and sugarcane ash) happened after them being spread on the subsoil surface. After six months, seedlings of ten Cerrado tree species were introduced randomly, in planting spacing of 4.0 x 5.0 m, totaling 1,080 seedlings. The experimental was a randomized block in a 3 x 4 factorial design, consisting of 3 doses of macrophytes (0, 16 and 32 t ha -1 ) and 4 ash levels (0, 15, 30 and 45 t ha -1 ), a total of 12 treatments, with 03 repetitions, established in plots 20 x 30 m (600 m 2 ), separated by 5 m wide ranges. After 24 months of experiment installation were evaluated: density, macro and microporosity, fertility, height and diameter of the plants, released CO 2 -carbon (CO 2 -C) and number of spores of arbuscular ...

Para que um subsolo exposto tenha restabelecido, mesmo que parcialmente, a dinâmica de seus atributos na camada superficial e, com isto, apresente condições para receber e dar suporte à vegetação de cerrado é necessário a utilização de técnicas específicas. Para acelerem esta etapa uma alternativa seria a introdução de resíduos, como as macrófitas aquáticas removidas das águas de represas de usinas hidrelétricas, como resíduo orgânico e cinza de bagaço de cana-de-açúcar produzida em usinas sucroalcooleiras, como resíduo agroindustrial. Desta forma, o objetivo do trabalho foi o condicionamento de um subsolo exposto no Cerrado por meio de resíduos e da revegetação. A área foco tem extensão de 10,66 km 2, em área contínua, localizada à margem direita do Rio Paraná e degradada na década de 60 durante construção da Usina Hidrelétrica de Ilha Solteira-SP. Realizou-se a caracterização inicial da área e as demais avaliações foram feitas após 12 e 24 meses da implantação do experimento. A área foi gradeada (grade pesada), para rompimento do encrostamento superficial e escarificada, à profundidade média de 0,37 m. A área foi novamente gradeada para desmanchar os torrões produzidos durante a subsolagem e para a incorporação dos resíduos (macrófitas aquáticas e cinza de cana-de-açúcar) distribuídos a lanço. Após seis meses, mudas de dez espécies arbóreas de Cerrado foram introduzidas aleatoriamente, no espaçamento de plantio 4,0 x 5,0 m, totalizando 1.080 mudas. O delineamento experimental foi o de blocos ao acaso, em esquema fatorial 3 x 4, sendo os tratamentos composto de 3 doses de macrófitas (0, 16 e 32 t ha -1 ) e 4 doses de cinza (0, 15, 30 e 45 t ha -1 ), totalizando 12 tratamentos, com 03 repetições, estabelecidos em parcelas de 20 x 30 m (600 m 2 ), separadas por faixas de 5 m de largura. Após 24 meses da instalação do experimento...
Keywords: Ecologia microbiana; Micorriza; Revegetação; Microbial ecology